Efisiensi Alokasi Dana Bantuan Operasional Sekolah (BOS) Pada Masa Pandemi Covid-19 - Noor, Triana Rosalina; Monita, Era (Universitas Negeri Surabaya, 2021)
The Covid-19 pandemic that occurred had an impact on the sustainability of educational institutions. In response, the government took a policy related to the flexibility of the use of School Operational Assistance (BOS) funds for educational institutions to be used based on the analysis of important needs to be met. The research method used is the study of literature with the topic of the efficiency of allocating BOS funds in the study of the concept of educational financial management. The results illustrate that in order for bos funding allocation to be efficient, it must pay attention and prioritize the principles of financial management, namely fairness, efficiency, transparency and public accountability. In addition, the process of planning, organizing, implementing and controlling is still carried out properly in accordance with standards. The factors supporting the success of BOS fund efficiency are HR factors, communication, clear organizational structure and attitudes from the leadership of an educational institution. The hope is that the use of BOS funds can be more useful and targeted to finance the learning needs of educational institutions affected by the Covid-19 pandemic.